Fabrication and Application of Silicotungstic Acid/Polyvinyl Alcohol and Phosphomolybdic Acid/Polyvinyl Alcohol Hybrid Membrane for Pervaporative Dehydration of Isopropanol Solution - Ünlü, Derya (Polymer Soc Korea, 2019)
Hybrid membranes were prepared by loading silicotungstic acid (STA) and phosphomolybdic acid (PMA), into polyvinyl alcohol (PVA) matrix. The membranes were characterized by Scanning electron microscopy (SEM), Fourier transform infrared (FTIR), contact angle meter, thermogravimetric analysis (TGA), and X-ray diffraction (XRD). Separation performance of hybrid PVA membranes was compared over that of neat PVA membrane, for dehydration of aqueous isopropanol mixtures by using the pervaporation (PV) process. The PV experiments were conducted over the feed water composition of 5-20 wt.%, temperature range of 3060 degrees C, and heteropolyacid amount of 5-20 wt%. Usage of hybrid membranes for separating water from the organic solvents, results in high flux and selectivity values. Of all the membranes studied, 5 wt% STA loaded hybrid PVA membrane and 5 wt% PMA loaded hybrid PVA membrane, exhibited best separation performance. While flux and selectivity values are 0.499 kg/m(2)h and 12848 for 5 wt% STA loaded hybrid PVA membrane, these values are 0.471 kg/m(2)h and 74991 for 5 wt% PMA loaded hybrid PVA membrane. Flux and selectivity values of neat PVA membrane are quite lower, as compared to the hybrid membranes. Neat PVA membrane has 0.360 kg/m(2)h of flux, and 36 of selectivity values. From this study, it is concluded that the selectivity and flux values of hybrid membranes, are rather higher than the neat PVA membrane.
Keywords: heteropolyacid; hybrid membrane; pervaporation; phosphomolybdic acid; silicotungstic acid